Alumina sintered compact and electrostatic chuck
Patent Information
- Application Number
- JP2024097826
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-06-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-18
AI Technical Summary
【0008】 この形態のアルミナ質焼結体によれば、イットリウムが添加されているため、アルミナ粒界を強化することができる。また、アルミナ質焼結体のカルシウム濃度が低いため、カルシウムとイットリウムとを含む2次相の析出を抑制することができる。さらに、アルミナ結晶粒子の平均粒径が6μm以下に制御されているため、2次相の析出を抑制することができる。これらの結果、この形態のアルミナ質焼結体によれば、パーティクルの発生を抑制することができる。
Smart Images

Figure 2025022755000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an alumina sintered body and an electrostatic chuck. [Background technology]
[0002] As semiconductors become finer, there are increasingly stringent requirements for ceramic members to suppress particle generation. Many particles from ceramics are caused by grain shedding, and there are methods for suppressing grain shedding by adding grain boundary strengthening elements (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4744855 [Patent Document 2] Patent Publication No. 2021-093488 Summary of the Invention [Problem to be solved by the invention]
[0004] However, if a ceramic contains a phase with a different composition from the base material, the difference in etching rate during plasma exposure can cause that layer to become convex, and it can become a particle when it is detached from the base material.
[0005] The present invention has been made to solve the above-mentioned problems, and has an object to provide a technique for suppressing generation of particles in an alumina sintered body. [Means for solving the problem]
[0006] The present invention has been made to solve at least one of the above problems, and can be realized in the following forms.
[0007] (1) According to one embodiment of the present invention, Al 2 O3 The alumina sintered body contains yttrium (Y) in an amount of 90 ppm or more and 265 ppm or less, calcium (Ca) in an amount of 100 ppm or less, and has an average grain size of alumina crystal grains of 6 μm or less.
[0008] According to the alumina sintered body of this embodiment, since yttrium is added, the alumina grain boundaries can be strengthened. Also, since the calcium concentration of the alumina sintered body is low, the precipitation of secondary phases containing calcium and yttrium can be suppressed. Furthermore, since the average grain size of the alumina crystal grains is controlled to 6 μm or less, the precipitation of secondary phases can be suppressed. As a result, according to the alumina sintered body of this embodiment, the generation of particles can be suppressed.
[0009] (2) In the alumina sintered body of the above embodiment, a peak corresponding to a lattice spacing of 2.6 Å to 2.9 Å may not be present in the measurement result of the alumina sintered body by X-ray diffraction method. 3 Al 5 O 12 Since almost no yttrium aluminum garnet (YAG) precipitates at the triple junctions of grain boundaries, the generation of particles can be suppressed.
[0010] (3) In the above-mentioned alumina sintered body, the surface of the alumina sintered body is observed by scanning electron microscope at a depth of 1.2 mm. 2 When checking the area of the calcium (Ca) and yttrium (Y), 2 The above phases may be present in one or less places. According to the alumina sintered body of this form, no phase containing calcium (Ca) and yttrium (Y) is detected, and the precipitation of secondary phases is suppressed, so that the generation of particles can be suppressed.
[0011] (4) In the above-mentioned alumina sintered body, the density is 3.96 g / cm 3In this way, the number of pores (voids) is small, so that generation of particles can be suppressed.
[0012] (5) According to another aspect of the present invention, there is provided an electrostatic chuck for holding an object, the electrostatic chuck comprising: a plate-shaped first layer having a first surface on which the object is placed and a second surface that is a surface opposite to the first surface; and a plate-shaped second layer disposed on the second surface side of the first layer and having a chuck electrode disposed therein, wherein at least a portion of the first surface of the first layer is formed of the alumina sintered body according to the above aspect.
[0013] According to the electrostatic chuck of this embodiment, at least a part of the first surface on which an object is placed is formed of the alumina sintered body of the above embodiment, so that the precipitation of secondary phases is suppressed on at least a part of the first surface, and therefore, when the first surface of the electrostatic chuck is irradiated with plasma, the generation of particles can be suppressed.
[0014] The present invention can be realized in various forms, for example, in the form of a semiconductor manufacturing equipment part, a semiconductor manufacturing equipment, a holding device, an electrostatic chuck, an apparatus including these, and a method for manufacturing a semiconductor manufacturing equipment part. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a process diagram showing a method for producing an alumina sintered body. [Diagram 2] FIG. 13 is a diagram showing the evaluation results of the examples. [Diagram 3] FIG. 1 is a diagram showing an example of the presence or absence of a Ca-Y phase in a sample. [Figure 4] FIG. 1 is a diagram showing the difference in precipitation of secondary phases depending on the firing time. [Diagram 5] FIG. 1 is an explanatory diagram conceptually showing the mechanism of secondary phase precipitation. [Figure 6] FIG. 13 is a diagram showing an example of an SEM image of a sample after plasma irradiation. [Figure 7]FIG. 11 is a perspective view illustrating an external configuration of an electrostatic chuck according to a second embodiment. [Figure 8] FIG. 2 is an explanatory diagram illustrating a schematic XZ cross-sectional configuration of the electrostatic chuck. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] First Embodiment The alumina sintered body according to the first embodiment of the present invention is made of alumina (Al 2 O 3 ) as the main component, containing yttrium (Y) at 90 ppm or more and 265 ppm or less, calcium (Ca) at 100 ppm or less, and the average grain size of the alumina crystal grains at 6 μm or less. The lower limit of the average grain size of the alumina crystal grains is not particularly limited, but it is preferably 0.5 μm or more. The alumina sintered body preferably does not contain calcium. However, calcium is likely to be mixed in as an impurity, and in the alumina sintered body of this embodiment, the calcium content is suppressed to 100 ppm or less as described above.
[0017] The yttrium and calcium contents can be determined as follows. The alumina sintered body is subjected to elemental analysis by ICP (Inductively Coupled Plasma) emission spectrometry to quantify the amount of yttrium and calcium. Since there is sampling variation in the measurement, the average value of 5 or more measurements is used.
[0018] In alumina sintered bodies, the addition of yttrium can strengthen the alumina grain boundaries, i.e., the bonds between alumina crystal grains become stronger (the bonding strength improves), and thus grain shedding can be suppressed. Gadolinium (Gd) is also an element that is effective in strengthening grain boundaries, but the addition of yttrium is preferable because it results in a higher withstand voltage than the addition of gadolinium.
[0019] Furthermore, when the alumina sintered body contains calcium, a phase (secondary phase) containing calcium and yttrium is precipitated. Since both calcium and yttrium are elements resistant to plasma, the precipitated secondary phase has a different etching rate from that of the alumina crystal grains when exposed to plasma, and the secondary phase portion (Ca-Y phase) remains as a convex, and is highly likely to become a particle. Furthermore, when calcium is contained during the production of the alumina sintered body, the grain growth of the alumina crystal grains is promoted, so the secondary phase is easily formed. In contrast, the alumina sintered body of this embodiment has a low calcium content of 100 ppm or less, so that the precipitation of a secondary phase with a composition different from that of the base material can be suppressed, and the generation of particles can be suppressed.
[0020] The grain size of the alumina crystal grains of the alumina sintered body can be measured by the intercept method. Specifically, the fracture surface of the alumina sintered body is observed by a SEM (Scanning Electron Microscope), and when a straight line of length L is drawn on the obtained secondary electron image, the number n of grains that the line crosses is measured. Note that grains with both ends of the line inside are counted as 0.5 grains. Then, the average grain size D (μm) is calculated by the following formula (1). D = 1.5 × L / n (1) In this embodiment, multiple average particle sizes D are obtained by drawing parallel lines of any number of lines intersecting with the number n of particles of 100 or more.
[0021] When alumina crystal grains grow abnormally, a secondary phase of YAG precipitates. By reducing the average grain size of alumina crystal grains to 6 μm or less, the generation of the secondary phase can be suppressed, and the formation of convex parts during plasma exposure can be suppressed, thereby suppressing the generation of particles.
[0022] In the alumina sintered body of this embodiment, it is preferable that there is no peak corresponding to a lattice spacing of 2.6 Å to 2.9 Å in the measurement result by X-ray diffraction. That is, the YAG maximum peak is not detected by X-ray diffraction of the alumina sintered body. Here, YAG has a maximum peak in the crystal orientation (3,1,1), which corresponds to the lattice spacing of 2.6 Å to 2.9 Å. In such an alumina sintered body, since YAG is hardly precipitated, the generation of particles can be suppressed.
[0023] The surface of the alumina sintered body of this embodiment was examined with a scanning electron microscope at a depth of 1.2 mm. 2 When checking the area of the calcium (Ca) and yttrium (Y), 2 It is preferable that the above phases exist in one place or less. In such an alumina-based sintered body, the precipitation of secondary phases containing calcium (Ca) and yttrium (Y) is suppressed, so that the generation of particles can be suppressed.
[0024] The density of the alumina sintered body of the present embodiment is not particularly limited, but is preferably 3.96 g / cm 3 It is preferable that the density of the alumina sintered body is equal to or higher than the theoretical density of alumina. Such an alumina sintered body has few pores (vacant holes), and therefore it is possible to suppress the generation of particles. The density of the alumina sintered body can be measured by Archimedes' method (JIS R 1634). The density of the alumina sintered body is preferably 4.0 g / cm3, which is the theoretical density of alumina. 3 It is preferable that the value is close to .
[0025] FIG. 1 is a process diagram showing a method for producing an alumina sintered body. In the method for producing an alumina sintered body of this embodiment, the steps are a blending and spray drying step P1, a degreasing step P2, and a hot pressing step P3 in that order. First, in the blending and spray drying step P1, an inorganic component and a binder dispersant are added to a solvent, and then pulverized and mixed in a ball mill. The inorganic component is alumina (Al 2 O 3 ) to yttria (Y 2 O 3 ) and spinel (MgAl 2 O 4) and other auxiliary materials are added. Spinel is added to suppress the grain growth of alumina. The slurry obtained from the ball mill is dried by spray drying to produce granules.
[0026] In the debinding process P2, the granules obtained in the blending and spray drying process P1 are uniaxially pressed (at about 10 MPa) and CIP (Cold Isostatic Pressing) (at about 150 MPa) to form a pressed body, which is then debound at 500 to 800°C.
[0027] In the hot pressing process P3, the degreased body obtained in the degreasing process P2 is hot pressed at 1300°C to 1625°C in an inert atmosphere (Ar, vacuum, etc.). This produces an alumina-based sintered body. In hot pressing, pressure is applied during sintering, which allows the particles to be crushed while sintering, compared to air sintering, and therefore promotes densification and makes it easier to reduce pores at grain boundaries. In addition, the contact area between particles is increased, so the sintering process itself can be completed in a shorter time than air sintering.
[0028] The alumina sintered body of the present embodiment can be used for semiconductor manufacturing device parts, semiconductor manufacturing devices, holding devices, electrostatic chucks, devices including these devices, and the like. EXAMPLES
[0029] The present invention will be explained more specifically with reference to examples. 2 is a diagram showing the evaluation results of Samples 1 to 18. Samples 1 to 18, which are alumina sintered bodies produced under different conditions, were evaluated for sintered density, average grain size, calcium content, and the presence or absence of Ca-Y phase and YAG phase.
[0030] 1. Sample Preparation Samples 1 to 18 were manufactured by the manufacturing method of the above embodiment. These samples differ from each other in the amounts of yttria and spinel added in the blending and spray drying step P1, the presence or absence of a dispersant added, and the firing temperature and firing time in the hot pressing step P3.
[0031] The amount of Y added (ppm) in FIG. 2 is calculated from the amount of yttria added. The yttrium content (ppm) in the alumina sintered body is approximately equal to the amount of yttrium added (ppm). The yttrium content can be determined by subjecting the alumina sintered body to elemental analysis using ICP optical emission spectrometry. However, since the sampling variation is about ±20%, the yttrium content (amount determined by ICP optical emission spectrometry) converges to the amount of yttrium added by measuring 5 or more samples and using the average value.
[0032] In the degreasing step P2, degreasing was performed in air at 500° C. In the hot pressing step P3, samples 1 to 15, 17, and 18 were pressed at a hot pressing pressure of 20 MPa, and sample 16 was pressed at a hot pressing pressure of 60 MPa. The firing temperature and firing time will be described later.
[0033] The manufacturing conditions of sample 4 (Y addition amount 174 ppm / firing temperature 1550°C / firing time 4 hours) were used as standard conditions, and the amount of yttrium added, the firing temperature, the firing time, and the presence or absence of dispersant addition were changed. The dispersant added here contains calcium, and it is considered that calcium promotes the growth of alumina crystal particles. In the examples, dispersants are added to samples 13 and 14, and no dispersant is added to the remaining samples. Dispersants containing calcium have the effect of suppressing the aggregation of inorganic components in the solvent. In samples 1 to 18, when a dispersant is added, water is used as the solvent. When no dispersant is added, an organic solvent (here, ethanol) is used as the solvent to suppress aggregation. In other examples, a dispersant not containing calcium may be used, and the solvent may be water. In addition, various known organic solvents other than those mentioned above may be used as the organic solvent.
[0034] 2.Measurement method The density of the alumina sintered body was measured by the Archimedes method (JIS R 1634).
[0035] The average grain size of the alumina crystal grains of the alumina sintered body was calculated using the grain sizes measured by the intercept method as described above.
[0036] The calcium content was determined by ICP emission spectrometry. Because there was variation in sampling during the measurement, the average value of five measurements was used. The presence or absence of Ca-Y phase was determined by checking SEM images of the fracture surface and mirror-polished surface of each sample, and by identifying the elements contained using EDS (energy dispersive X-ray spectroscopy). The presence or absence of YAG phase was determined by XRD (X-ray diffraction).
[0037] 3.Measurement results FIG. 3 is a diagram showing an example of the presence or absence of a Ca-Y phase in a sample. FIGS. 3(A) to (C) show SEM images of samples 4, 13, and 15, respectively, and FIG. 3(D) shows the result of EDS of sample 13. The spectrum is shown on the left side of FIG. 3(D), and the quantitative results are shown on the right side. FIG. 4 is a diagram showing the difference in precipitation of secondary phases depending on the firing time. FIG. 5 is an explanatory diagram conceptually showing the mechanism of secondary phase precipitation. FIG. 6 is a diagram showing an example of an SEM image of a sample after plasma irradiation.
[0038] Sample 4 (alumina sintered body 100) manufactured under standard conditions satisfies the following requirements [1] to [6] (FIG. 2). [1] Contains yttrium (Y) in amounts of 90 ppm or more and 265 ppm or less. [2] Contains less than 100 ppm of calcium (Ca). [3] The average grain size of the alumina crystal grains is 6 μm or less. [4] In the X-ray diffraction measurement of the alumina sintered body, there is no peak corresponding to the lattice spacing of 2.6 Å to 2.9 Å. In other words, there is no YAG phase. [5] The surface of the alumina sintered body was examined with a scanning electron microscope at 1.2 mm 2 When checking the area of the calcium (Ca) and yttrium (Y), 2 The above phases are present in one place or less. In other words, there is no Ca-Y phase. [6] The density of sintered alumina is 3.96 g / cm3 That's all.
[0039] 3(A) is an SEM image of the surface (mirror polished) of Sample 4. As shown in the figure, in the SEM image of Sample 4, no precipitation of a secondary phase is confirmed.
[0040] Samples 3, 5 to 7, 17, and 18 were produced by changing only the sintering temperature of Sample 4. Samples 3, 17, and 18 were produced at sintering temperatures of 1525°C, 1450°C, and 1490°C, respectively, which are lower than Sample 4. Samples 5 to 7 were produced at sintering temperatures of 1575°C, 1600°C, and 1625°C, respectively, which are higher than Sample 4. Sample 3 has the same sintered density as Sample 4, and an average grain size smaller than Sample 4. Samples 5 and 6 have a smaller sintered density than Sample 4, and an average grain size larger than Sample 4. Sample 7 has a larger sintered density and average grain size than Sample 4. Samples 17 and 18 have a smaller sintered density and average grain size than Sample 4. Samples 3, 5 to 7, 17, and 18 also meet the above requirements [1] to [6]. In other words, Ca-Y phase and YAG phase (secondary phase) are not formed. Moreover, from the results of Samples 3 to 7, 17, and 18, it can be seen that the higher the firing temperature, the larger the average particle size.
[0041] Sample 2 has a smaller amount of Mg (added as spinel) than Sample 4, but the other conditions are the same as Sample 4. Sample 2 has a larger sintered density than Sample 4, and the same average grain size as Sample 4. Sample 2 also satisfies the above requirements [1] to [6]. In other words, no Ca-Y phase or YAG phase (secondary phase) is formed.
[0042] Sample 1 has a smaller amount of yttrium added (87 ppm) than Sample 4, but the other conditions are the same as Sample 4. Sample 1 has the same sintered density as Sample 4, and a smaller average grain size. Sample 1 also satisfies the above requirements (1) to (6). In other words, no Ca-Y phase or YAG phase (secondary phase) is formed.
[0043] Compared to Sample 4, Sample 8 had a higher firing temperature of 1625°C and a significantly longer firing time of 12 hours. Other conditions were the same as Sample 4. Sample 8 had an average alumina crystal grain size of 7.5 μm, which was larger than that of Sample 4, and a YAG phase (secondary phase) was formed. Among the above requirements [1] to [6], Sample 8 does not satisfy [3] and [4].
[0044] Compared to Sample 4, Sample 16 has a lower sintering temperature of 1300°C and a higher hot press pressure of 60 MPa. The other conditions are the same as Sample 4. Sample 16 has a smaller sintered density and average grain size than Sample 4. Sample 16 also meets the above requirements (1) to (6). In other words, no Ca-Y phase or YAG phase (secondary phase) is formed. As mentioned above, the lower the sintering temperature, the smaller the average grain size of the alumina crystal grains. However, if the sintering temperature is too low, the material will not harden, so the hot press pressure is higher in Sample 16.
[0045] FIG. 4(A) shows SEM images (channeling contrast images) of Sample 7 and Sample 8. Sample 7 and Sample 8 were fired for different times, 4 hours and 8 hours, but the other conditions were the same. As shown in FIG. 4(A), Sample 7 had little precipitation of the secondary phase, and the thickness of the sample was 22.5 mm. 2 On the other hand, sample 8 had many secondary phases precipitated, and the secondary phases were observed in only two places in the field of view of 22.5 mm. 2 The secondary phase was confirmed in 14 places in the field of view. By extending the firing time from 4 hours to 12 hours, the growth of alumina crystal grains and the increase of the secondary phase were confirmed.
[0046] Figure 4(B) shows the results of XRD for samples 7 and 8. A peak consistent with YAG was confirmed in sample 8. Therefore, the secondary phase of sample 8 was determined to be YAG. Here, the wavelength of the X-rays was 1.5418 Å (characteristic X-rays of Cu Kα).
[0047] The secondary phase is believed to precipitate as follows. As shown in the upper part of Fig. 5, at the start of the sintering process (hot pressing process P3), yttrium 1 is present at the alumina crystal grain boundaries. The secondary phase 2 precipitates due to a decrease in the grain boundary area accompanying the growth of alumina crystal particles 10 (middle part of Fig. 5). Diffusion through the secondary phase causes abnormal grain growth, which further reduces the grain boundary area and causes the secondary phase to cluster (lower part of Fig. 5).
[0048] As shown in FIG. 2, Samples 9 to 11 have a larger amount of yttrium added than Sample 4, at 209 ppm, 261 ppm, and 348 ppm, respectively, and the other conditions are the same as Sample 4. Sample 9 has the same sintered density as Sample 4, and the average grain size is slightly larger than that of Sample 4. Sample 9 satisfies the above requirements [1] to [6]. Sample 10 has a slightly larger sintered density than Sample 4, and the average grain size is the same as that of Sample 4. Sample 10 satisfies the above requirements [1] to [6]. In other words, secondary phases of Ca-Y phase and YAG phase are not formed in Samples 9 and 10.
[0049] Sample 11 has the same sintered density as Sample 4, the average grain size of the alumina crystal grains is slightly larger than that of Sample 4, and a YAG phase (secondary phase) is formed. Sample 11 does not satisfy requirement (4) among the above requirements (1) to (6). It is considered that, due to the large amount of yttrium added in Sample 11, some of the yttrium could not exist in the grain boundaries of the alumina crystal grains and precipitated as a secondary phase.
[0050] Sample 12 has a smaller amount of magnesium added than Sample 4, but the other conditions are the same as Sample 4. Sample 12 has a slightly higher sintered density and a slightly smaller average grain size than Sample 4. Sample 12 also satisfies the above requirements [1] to [6]. In other words, secondary phases of Ca-Y phase and YAG phase are not formed.
[0051] Samples 13 and 14 were prepared under the same conditions as Sample 4, except that a dispersant containing calcium was added. Sample 13 contained 103 ppm calcium, and its sintered density and average grain size were slightly larger than those of Sample 4. A Ca-Y phase (secondary phase) was formed. In the SEM image of the sample surface shown on the left side of Figure 3(B), a secondary phase was confirmed in the circled area. Furthermore, the EDS results for Sample 13 confirmed the precipitation of calcium (Figure 3(D)). Sample 13 does not meet the requirements of [2] and [5] above.
[0052] Sample 14 has a calcium content of 175 ppm, a sintered density slightly larger than that of Sample 4, and an average grain size of 7.2 μm, which is larger than that of Sample 4. Sample 14 has both Ca-Y and YAG secondary phases formed. In other words, Sample 13 does not satisfy the above requirements [2] to [5].
[0053] Sample 15 contains more than four times as much yttrium as Sample 4, and is fired at a high temperature of 1600°C, but the other conditions are the same as Sample 4. Sample 14 has the same sintered density as Sample 4, but the average grain size is larger than Sample 4 at 6.2 μm, and a YAG phase (secondary phase) is formed. In the SEM image of the sample surface shown on the left side of Figure 3(C), a secondary phase was confirmed in the circled area. Sample 15 does not satisfy the above requirements [3] and [4].
[0054] The example shown in FIG. 6 is an SEM image after a sample was irradiated with plasma under the following conditions. Plasma irradiation Method: ICP Gas:CF 4 +O 2 Source RF: 1000W Bias RF: 300W Irradiation time: 5 minutes
[0055] As described above, in sample 4 shown in Fig. 6(A), no secondary phase (YAG phase, Ca-Y phase) is formed, and no protrusions are formed on the surface after plasma irradiation. On the other hand, in sample 15 shown in Fig. 6(B), as described above, a secondary phase (YAG phase) is formed, and secondary phase 2 (YAG phase) remains in a protruding shape on the surface after plasma irradiation.
[0056] As described above, Samples 1 to 7, 9, 10, 12, and 16 to 18 satisfy all of the requirements [1] to [6] above, and are examples of the alumina-based sintered body 100 of the above embodiment. Since no secondary phase is formed in these samples, the generation of particles can be suppressed when exposed to plasma.
[0057] <Second embodiment> Fig. 7 is a perspective view that shows a schematic external configuration of an electrostatic chuck 1000 according to a second embodiment of the present invention. Fig. 8 is an explanatory diagram that shows a schematic XZ cross-sectional configuration of the electrostatic chuck 1000. In Figs. 7 and 8, mutually orthogonal X, Y and Z axes are shown to specify the directions. In Fig. 8, the positive Y direction is the direction toward the back side of the paper. In this specification, for convenience, the positive Z direction is referred to as the upward direction and the negative Z direction is referred to as the downward direction, but the electrostatic chuck 1000 may actually be installed in a direction different from these directions.
[0058] The electrostatic chuck 1000 is a device that attracts and holds an object (e.g., a wafer W) by electrostatic attraction, and is used, for example, to fix the wafer W in a vacuum chamber of a semiconductor manufacturing device. The electrostatic chuck 1000 includes a first layer 110, a second layer 200, a cooling section 300, and a joining section 400 that is arranged between the second layer 200 and the cooling section 300 and joins the second layer 200 and the cooling section 300, which are arranged in a vertical direction (Z-axis direction).
[0059] The first layer 110 is a plate-like member having a first surface S1 having a circular flat shape and a second surface S2 which is a surface opposite to the first surface S1 and also has a circular flat shape. In this embodiment, the first surface S1 of the first layer 110 functions as a mounting surface on which a wafer W is mounted. The first layer 110 is formed of the alumina sintered body 100 of the first embodiment. The porosity of the first layer 110 is 1% or less.
[0060] The second layer 200 is a plate-like member having a third surface S3 and a fourth surface S4 which is the reverse side of the third surface S3. In detail, the second layer 200 is a plate-like member which includes a second layer main body 210 (FIG. 1) which is a plate-like member having a third surface S3 of a substantially circular planar shape, and a flange portion 220 (FIG. 1) which protrudes from the second layer main body 210, and which expands in diameter in a stepped manner downward (toward the negative Z-axis direction) as a whole. As shown in the figure, the third surface S3 has substantially the same planar shape as the second surface S2, and the fourth surface S4 expands in diameter more than the third surface S3.
[0061] The second layer 200 is a dense body mainly composed of ceramics, so-called fine ceramics or new ceramics. However, the porosity of the second layer 200 is larger than that of the first layer 110, and is 1% to 5%. Examples of ceramics include alumina (Al 2 O 3 ), aluminum nitride (AlN), zirconia (ZrO 2 ), silicon carbide (SiC), zircon (ZrO 2 SiO 2 ), Mullite (3Al 2 O 3 2SiO 2 ), silicon nitride (Si 3 N 4 It is preferable that the main component of the second layer 200 is alumina, which is the same as the main component of the first layer 110, because this makes it possible to keep the difference in thermal expansion coefficient between the first layer 110 and the second layer 200 small.
[0062] A chuck electrode 230 (FIG. 8) made of a conductive material (e.g., tungsten, molybdenum, etc.) is disposed inside the second layer 200. The shape of the chuck electrode 230 as viewed in the Z-axis direction is, for example, circular. When a voltage is applied to the chuck electrode 230 from a power source (not shown), an electrostatic force is generated, and the wafer W is attracted and fixed to the first surface S1 of the first layer 110 by this electrostatic force.
[0063] Further, inside the second layer 200, a heater 240 (FIG. 8) is disposed below the chuck electrode 230 (Z-axis negative side) and has a spiral shape as viewed in the Z-axis direction. In this embodiment, the heater 240 is a metallized layer formed of tungsten, molybdenum, or the like. The shape of the heater 240 is not limited to this embodiment, and may be, for example, a disk shape. In other embodiments, the second layer 200 may not include the heater 240.
[0064] In this embodiment, the first layer 110 and the second layer 200 are bonded by diffusion bonding. In other embodiments, the first layer 110 and the second layer 200 may be bonded using the same material (so-called supply material) as the first layer 110 or the second layer 200. By bonding the first layer 110 and the second layer 200 without using an adhesive mainly composed of an organic material, it is possible to suppress a decrease in heat transfer between the first layer 110 and the cooling section 300.
[0065] The cooling part 300 is a circular, flat, plate-like member having a diameter larger than that of the fourth surface S4 of the second layer 200. The cooling part 300 is made of a metal with high thermal conductivity. For example, aluminum, titanium, molybdenum, or an alloy containing each of these as a main component can be used. The diameter of the cooling part 300 is, for example, about 220 mm to 550 mm (usually 220 mm to 350 mm), and the thickness of the cooling part 300 is, for example, about 20 mm to 40 mm.
[0066] A coolant flow passage 310 (FIG. 8) is formed inside the cooling part 300. When the wafer W held on the first layer 110 of the electrostatic chuck 1000 is processed using plasma, heat is input from the plasma to the wafer W, and the temperature of the wafer W rises. When a coolant (e.g., a fluorine-based inert liquid or water) flows through the coolant flow passage 310 formed in the cooling part 300, the cooling part 300 is cooled. The first layer 110 is cooled by heat transfer between the cooling part 300 and the first layer 110 via the second layer 200 and the bonding part 400, and the wafer W held on the first surface S1 of the first layer 110 is cooled. This realizes temperature control of the wafer W. In other embodiments, the cooling part may not have a coolant flow passage formed therein, and may be cooled from the outside.
[0067] The bonding part 400 is a circular flat plate-like member having a diameter equal to that of the first surface S1, and bonds the second layer 20000 and the cooling part 300. The bonding part 400 is formed from an adhesive containing an organic material as a main component, and examples of the organic material that can be used include silicone, acrylic, polyimide, and the like.
[0068] According to the electrostatic chuck 1000 of this embodiment, a mounting surface (first surface S1) on which a wafer W is mounted is formed by the alumina sintered body 100 of the first embodiment. When the wafer W held by the electrostatic chuck 1000 is processed using plasma, the first layer 110 is exposed to the plasma more than the second layer 200 and the cooling part 300. In the electrostatic chuck 1000 of this embodiment, the alumina sintered body 100 of the first embodiment is disposed at a location that is more exposed to the plasma, and the alumina sintered body 100 can suppress the generation of particles when exposed to plasma. Therefore, when the electrostatic chuck 1000 of this embodiment is used, the generation of particles can be suppressed when the wafer W is subjected to plasma processing.
[0069] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.
[0070] The method for producing the alumina sintered body is not limited to the above embodiment. By appropriately changing the type of dispersant, the amount of dispersant added, the firing method, the firing atmosphere, the firing temperature, the hot press pressure, etc., it is possible to produce an alumina sintered body containing yttrium (Y) of 90 ppm to 265 ppm, calcium (Ca) of 100 ppm or less, and an average grain size of alumina crystal grains of 6 μm or less. In addition, it may be produced by other known methods such as a gel casting method.
[0071] In the above embodiment, impurities other than yttrium, calcium, and magnesium may be contained, however, it is preferable that the alloy does not contain other impurities, since this can suppress the precipitation of secondary phases.
[0072] In the above second embodiment, an example has been shown in which the entire first surface S1 of the first layer 110 is formed of the alumina sintered body 100 of the first embodiment, but it is sufficient that at least a portion of the first surface S1 of the first layer 110 is formed of the alumina sintered body 100 of the first embodiment. For example, a portion including a portion that is exposed and not covered by the wafer W when the wafer W is placed on the first surface S1 may be formed of the alumina sintered body 100 of the first embodiment. This also makes it possible to suppress the generation of particles.
[0073] In the second embodiment, the electrostatic chuck 1000 may have a flow path for flowing a gas such as helium (He) gas between the attracted wafer W and the first surface S1.
[0074] The present invention has been described above based on the embodiments, examples, and modified examples, but the above-mentioned embodiments are intended to facilitate understanding of the present invention and do not limit the present invention. The present invention may be modified or improved without departing from the spirit and scope of the claims, and the present invention includes equivalents thereof. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate.
[0075] The present invention can also be realized as the following application examples. [Application example 1] Al 2 O 3 An alumina sintered body mainly composed of Contains yttrium (Y) in amounts of 90 ppm or more and 265 ppm or less. Contains calcium (Ca) at less than 100 ppm, The average particle size of the alumina crystal particles is 6 μm or less. Alumina sintered body. [Application example 2] The alumina sintered body according to Application Example 1, The alumina sintered body is characterized in that, in the measurement result by the X-ray diffraction method, there is no peak corresponding to a lattice spacing of 2.6 Å to 2.9 Å. Alumina sintered body. [Application example 3] The alumina sintered body according to Application Example 1 or Application Example 2, The surface of the alumina sintered body was examined by a scanning electron microscope at 1.2 mm 2 When checking the area of the calcium (Ca) and yttrium (Y), 2 The above phase is present in one or less places, Alumina sintered body. [Application example 4] The alumina sintered body according to any one of Application Examples 1 to 3, Density 3.96g / cm 3 The above is characterized in that Alumina sintered body. [Application example 5] 1. An electrostatic chuck for holding an object, comprising: a plate-like first layer having a first surface on which the object is placed and a second surface that is the reverse side of the first surface; a plate-shaped second layer disposed on the two surfaces of the first layer and having a chuck electrode disposed therein; Equipped with At least a part of the first surface of the first layer is formed of the alumina sintered body according to any one of Application Examples 1 to 4. Electrostatic chuck. [Explanation of symbols]
[0076] 1…Yttrium 2…Second phase 10...Alumina crystal particles 100...Alumina sintered body 110…1st layer 200…Second layer 210...2nd layer main body 220…Flange 300...Cooling section 400…Joint part 1000...Electrostatic chuck S1...Side 1 S2...Side 2 S3...Side 3 S4...Side 4
Claims
1. A 2 O 3 An alumina sintered body having as its main component Contains yttrium (Y) in an amount of 90 ppm or more and 265 ppm or less, Contains calcium (Ca) at 100 ppm or less, The average particle size of the alumina crystal particles is 6 μm or less. Alumina sintered body.
2. The alumina sintered body according to claim 1, The alumina sintered body is characterized in that, in the measurement result by the X-ray diffraction method, there is no peak corresponding to a lattice spacing of 2.6 Å to 2.9 Å. Alumina sintered body.
3. The alumina sintered body according to claim 1, The surface of the alumina sintered body was examined by a scanning electron microscope at 1.2 mm 2 When the area of the calcium (Ca) and yttrium (Y) was confirmed, 2 The above phase is present in one or less places. Alumina sintered body.
4. The alumina sintered body according to claim 1, Density is 3.96 g / cm 3 The above is characterized in that Alumina sintered body.
5. 1. An electrostatic chuck for holding an object, comprising: a plate-like first layer having a first surface on which the object is placed and a second surface that is a reverse surface of the first surface; a plate-shaped second layer disposed on the second surface side of the first layer and having a chuck electrode disposed therein; Equipped with At least a part of the first surface of the first layer is formed of the alumina sintered body according to any one of claims 1 to 4. Electrostatic chuck.
Citation Information
Patent Citations
Alumina ceramic and its production
JP1997052758A
Alumina sintered compact
JP2001287983A
Thermal shock resistance and corrosion resistance and member for heat-treatment using the same
JP2005112635A
Electrostatic chuck and manufacturing method therefor, and alumina sintered member and manufacturing method therefor
JP2005210077A
Electrostatic chuck with heater and its manufacturing method
JP2008053316A
Cited By
Component for semiconductor manufacturing apparatus and method for regenerating the same
CN122910695A